2023
DOI: 10.29333/ejmste/13216
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of STEM education: A bibliometrics analysis from case study research in Scopus database

Abstract: In response to the long-term challenges of skills shortages and mismatches, many countries worldwide have made significant investments in STEM education. However, to obtain a comprehensive understanding of the progress of global research on the implementation of STEM education, it is essential to compile case studies on STEM education. Therefore, we conducted a bibliometric analysis of 750 publications from Scopus database to assess the bibliographic content of case studies on STEM education from 2006 to 2022.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
5
11
0
1
Order By: Relevance
“…Secondly, specialized literature on information technologies in adapted education grew since 2003, with the topics of the articles changing accordingly, while they were published in discrete journals (Mentel et al, 2023). Thirdly, research on case studies in innovations in science education has grown enormously and continuously over the last five years, with three main research directions identified: STEM education at higher education institutions, STEM education that also includes arts and cognates and STEM education tasks at K-12 education (Phuong et al, 2023). Finally, through the analysis of articles of technology in science education using bibliometrics, researchers unleash vital information, which highlights the relationship between science education and technology according to Bozkurt and Ozturk (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, specialized literature on information technologies in adapted education grew since 2003, with the topics of the articles changing accordingly, while they were published in discrete journals (Mentel et al, 2023). Thirdly, research on case studies in innovations in science education has grown enormously and continuously over the last five years, with three main research directions identified: STEM education at higher education institutions, STEM education that also includes arts and cognates and STEM education tasks at K-12 education (Phuong et al, 2023). Finally, through the analysis of articles of technology in science education using bibliometrics, researchers unleash vital information, which highlights the relationship between science education and technology according to Bozkurt and Ozturk (2022).…”
Section: Discussionmentioning
confidence: 99%
“…To collect all the publications on CT in mathematics learning, the data was extracted from the Scopus database (https://www.scopus.com) on 16 May 2023, with the central theme 'computational thinking'. According to Phuong et al (2023), the Scopus database is the most comprehensive and widely used academic database. For this study, the Scopus database was considered for five reasons: it provides relevant and reliable information, has broader coverage, includes all cited authors in the references, permits direct data download, and can be processed by various bibliometric analysis software (Gao et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…("MINT" being the German acronym for STEM) was developed for pre-service and in-service teachers in elementary education. Thus, a target group that is still underrepresented in STEM education research (Phuong et al, 2023) was addressed.…”
Section: Development Of Education and Further Trainingmentioning
confidence: 99%
“…The study was targeted at an important but still under-researched group in STEM, which according to Phuong et al (2023) is in need of support and more research: elementary education students and their teachers. International achievement tests like TIMSS identify challenges for the development of STEM competencies in this cohort of students, with girls being particularly impacted (Itzlinger-Bruneforth, 2020).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%